Clinical Presentation of Uterine Leiomyoma and the Outcome of Surgical Management Options in a Nigerian Tertiary Health Facility - Senbanjo OC; Ottun TA; Akinlusi FM; Oshodi YA; Rabiu KA; Adewunmi AA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: Effective treatment intervention for uterine leiomyoma is essential to prevent morbidities and associated potential mortalities. Objective: To determine the prevalence, clinical presentation of uterine leiomyoma and the outcome of surgical management options at the Lagos State University Teaching Hospital (LASUTH), Ikeja, Lagos, Nigeria. Methods: This was a descriptive retrospective study of cases of uterine leiomyoma from 01 January 2012 to 31 December 2016. The medical records of all patients with the diagnosis of leiomyoma were retrieved. Information was obtained on socio-demographics, clinical presentation, types of surgical treatment and associated postoperative complications. Results: Three hundred and thirty-five cases of leiomyoma were managed out of 1835 major gynaecological cases giving a period prevalence of 18.3%. However, only 134 case folders were available for analysis. The mean age of the women was 38.5±6.7 years. Only 21 (15.7%) cases presented within a year of the onset of symptoms. The surgical interventions used included myomectomy and hysterectomy but the former was the commonest with a frequency of 73.4%. There were no significant differences in the prevalence of postoperative complications between patients who had myomectomy and hysterectomy (p>0.05 in each case). Conclusion: Uterine leiomyoma is a common gynaecological condition. There is a need to create awareness of the need to present early to the hospital so that less invasive treatment options can be explored.